Data segmentation methods and algorithms - Nurmamatov Mekhriddin Kahramonovich (Peerian Journals Publishing, 2025)
With the rapid growth of information volume, almost all databases have data redundancy or insufficiency. In the process of data matching, quality issues are particularly important. In this case, the combination of data properties such as accuracy, completeness, relevance, viability, availability, and reliability determines the quality indicators in the database. As a result of the study of segmentation methods and algorithms, it can be used to match or remove duplicate attribute values. One of the main parts of segmentation is the implementation of names and addresses using rulebased methods. Implementing segmentation based on this technology significantly increases productivity.
Keywords: Segmentation; Attribute; Matching